Legal Instruments for the Collaboration of Divided Cities with Polish Constituents in Municipal Services Management - Brzozowski, Przemyslaw (Border Crossing, 2022)
One of the principal tasks of regional and local authorities in any state is to manage municipal services for the people living in the area. In the case of divided cities, or cities intersected by national borders, municipal services are, in principle, provided separately for the residents of each state. The author presents a definition of divided cities and the matter of potential collaboration between such cities in the area of joint management of municipal services. The article also attempts to answer the question, among others, what legal instruments may be applied in this respect and what benefits would be brought by municipal collaboration between divided cities. Furthermore, the author presents the current status of collaboration between divided cities in the area concerned.